Anti-oxidant, pediculicidal and pesticidal activities of leaves of Rhinacanthus nasutus (Linn) grown in Sri Lanka - Bulugahapitiya, Vajira P; PTN, Fernando; HD, Jayasekara (Asian Journal of Medical and Biological Research, 2021)
Rhinacanthus nasutus is an ethnomedical plant used in the traditional system of medicine for treating skin diseases. As no adequate studies available on R. nasutus grown in Sri Lanka, this study aimed on exploring anti-oxidant, anti-parasitic and pesticidal activity of leaves of the plant. Antioxidant capacity of the crude extract of leaves was evaluated using DPPH free radical scavenging assay and FRAP assay using ascorbic acid and FeSO4.7H2O as the standards respectively. Pediculicidal efficacy was carried out against head lice using 0.0010% (w/v) methanolic, ethyl acetate and aqueous extracts of leaves by following modified filter paper diffusion bioassay. Pesticidal activity of leaves was evaluated using modified filter paper contact bioassay against mealybugs, P. marginatus, resides on papaw and guava trees. The IC50 value of DPPH assay was found to be 514.3 μgmL-1 and FRAP value was found to be 594.33±2.93 μmol Fe2+/g in anti-oxidant assay. The LT50 (median Lethal Time) values for 0.0010% (w/v) concentration of methanolic, ethyl acetate and aqueous extracts were 263, 347 and 676 min respectively in pediculicidal assay. LC50 (50% mortality) value was found to be 0.0011% (w/v) after 240 minutes whereas LT50 values of 0.0020% (w/v) of methanol, ethyl acetate and aqueous fractions of R. nasutus for adult were found as 31, 124 and 189 hours and for nymph were 14, 18 and 29 hours respectively in pesticidal assay. Accordingly, methanolic extract was effective in controlling nymph stage of mealybug life cycle than adults with the LC50 of 0.0015% (w/v) within 14 hours. This study confirmed promising pediculicidal and pesticidal activity and significant anti-oxidant capacity of leaves of R. nasutus. Asian J. Med. Biol. Res. December 2020, 6(4): 754-760